Sodium-Glucose Co-Transporters Family: Current Evidence, Clinical Applications and Perspectives - Riccardo Nevola; Angela Villani; Simona Imbriani; Maria Alfano; Livio Criscuolo; Domenico Beccia; Rachele Ruocco; Augusto Delle Femine; Felice Gragnano; Domenico Cozzolino; Raffaele Marfella; Luigi Elio Adinolfi; et al. (Frontiers in Bioscience-Landmark, 2023)
Sodium-glucose co-transporters (SGLTs) family members are involved in several vital biological functions. Except for SGLT3, they are involved in the mechanisms of active transport of sodium and glucose and several micromolecules. The discovery of functions and mechanisms of SGLT1 inhibition and, in particular, of SGLT2 has radically changed the natural history of some pathologies. SGLT2 inhibitors have revolutionized the therapeutic approach not only of type 2 diabetes mellitus but also of heart failure and chronic kidney failure. Considering the role played by the other SGLTs and the functions still unknown to date, clinical implications of the inhibition of SGLT2 could represent the prelude for a wider modulation of these cotransporters. A better understanding of the role and function of SGLTs could represent a revolution in the therapeutic approach in the hepatological, metabolic, neurological and oncological fields. The purpose of this review is to illustrate the knowledge currently available on SGLTs, its clinical implications and future perspectives.